2022
DOI: 10.1371/journal.pone.0268071
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of infection prevention and control practices in an upcoming COVID-19 hospital in India: An opportunity not missed

Abstract: Infection prevention and control (IPC) program is obligatory for delivering quality services in any healthcare setup. Lack of administrative support and resource-constraints (under-staffing, inadequate funds) were primary barriers to successful implementation of IPC practices in majority of the hospitals in the developing countries. The Coronavirus Disease 2019 (COVID-19) brought a unique opportunity to improve the IPC program in these hospitals. A PDSA (Plan—Do—Study- Act) model was adopted for this study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The Indirect costs for patients and caregivers are displayed in Table 4 . Patients reported they were back to normalcy after a median (IQR) of 25 [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ] days (P=0.219). Of the 52 employed, 7 patients did not return to work due to illness, and 28 reported suboptimal efficiency at work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Indirect costs for patients and caregivers are displayed in Table 4 . Patients reported they were back to normalcy after a median (IQR) of 25 [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ] days (P=0.219). Of the 52 employed, 7 patients did not return to work due to illness, and 28 reported suboptimal efficiency at work.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that reviewed prescriptions during COVID reported up to 72% of hospitalised patients received antibiotics despite confirmed bacterial isolation in only 3 to 15% [ 28 ]. Another crucial driver of cost was ensuring the safety and protection of health workers via PPE gowns, single-use equipment and infrastructure to set up Covid wards [ 29 , 30 ]. The scarce supply during the pandemic also drove up the unit price of these resources.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Argya das et al (8) a total of 2552 health care professionals and 548 medical students were trained in IPC through multiple offline/onsite sessions over a period of 15 months during the ongoing pandemic (8) The overall compliance to surface disinfection and cleaning increased from 50% to >80% with repeated training, compliance decreased whenever newly recruited HCP were posted. (8) Hand hygiene compliance was poor varying from 10 to 40% complete adherence rate. (8) Fear psychosis in the pandemic was the greatest facilitator for adopting the IPC practices.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Hand hygiene compliance was poor varying from 10 to 40% complete adherence rate. (8) Fear psychosis in the pandemic was the greatest facilitator for adopting the IPC practices. (8) Continuous wearing of personal protective equipment for long duration, dissatisfaction with the duty rosters as well as continuous posting in high-risk areas were the major obstacles to the implementation of IPC norms (8) The present study found that 94% of the PHCs had the availability of PPEs and 94% had availability of soap and water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation